2009
DOI: 10.1002/bin.270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjusting DRO schedules on the reduction of stereotypic vocalizations in children with autism

Abstract: The reduction of stereotypic behavior is important for individuals with developmental disabilities because it may interfere with learning new skills. A common procedure used to reduce stereotypic behavior is differential reinforcement of other behavior (DRO). A DRO schedule is a procedure in which reinforcement is delivered given the absence of a target response for a period of time. Although DRO schedules have been shown to be effective in reducing a variety of stereotypic behavior, empirical studies have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In the case of vocal stereotypy, matched stimulation typically involves continuous access to stimuli that produce auditory stimulation. When compared with other interventions for vocal stereotypy such as differential reinforcement of other behaviors (e.g., Rozenblat, Brown, Brown, Reeve, & Reeve, 2009;Taylor, Hoch, & Weissman, 2005) and response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007;Miguel, Clark, Tereshko, & Ahearn, 2009), a potential advantage of providing matched stimulation is that the procedures do not require the undivided attention of a trainer. When compared with other interventions for vocal stereotypy such as differential reinforcement of other behaviors (e.g., Rozenblat, Brown, Brown, Reeve, & Reeve, 2009;Taylor, Hoch, & Weissman, 2005) and response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007;Miguel, Clark, Tereshko, & Ahearn, 2009), a potential advantage of providing matched stimulation is that the procedures do not require the undivided attention of a trainer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of vocal stereotypy, matched stimulation typically involves continuous access to stimuli that produce auditory stimulation. When compared with other interventions for vocal stereotypy such as differential reinforcement of other behaviors (e.g., Rozenblat, Brown, Brown, Reeve, & Reeve, 2009;Taylor, Hoch, & Weissman, 2005) and response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007;Miguel, Clark, Tereshko, & Ahearn, 2009), a potential advantage of providing matched stimulation is that the procedures do not require the undivided attention of a trainer. When compared with other interventions for vocal stereotypy such as differential reinforcement of other behaviors (e.g., Rozenblat, Brown, Brown, Reeve, & Reeve, 2009;Taylor, Hoch, & Weissman, 2005) and response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007;Miguel, Clark, Tereshko, & Ahearn, 2009), a potential advantage of providing matched stimulation is that the procedures do not require the undivided attention of a trainer.…”
mentioning
confidence: 99%
“…For example, Saylor et al (2012) have shown that providing noncontingent access to music may decrease engagement in vocal stereotypy in children with autism. When compared with other interventions for vocal stereotypy such as differential reinforcement of other behaviors (e.g., Rozenblat, Brown, Brown, Reeve, & Reeve, 2009;Taylor, Hoch, & Weissman, 2005) and response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007;Miguel, Clark, Tereshko, & Ahearn, 2009), a potential advantage of providing matched stimulation is that the procedures do not require the undivided attention of a trainer. Thus, the intervention is well-suited for free periods (e.g., breaks and play periods) during which the trainer may need to attend to other tasks.…”
mentioning
confidence: 99%
“…Researchers have shown that the noncontingent delivery of a stimulus that putatively matches the sensory product of stereotypy (i.e., noncontingent matched stimulation [NMS]) and the delivery of a reinforcer for the nonoccurrence of stereotypy (i.e., differential reinforcement of other behavior [DRO]) are both effective procedures to reduce the occurrence of stereotypic behavior (e.g., Patel, Carr, Kim, Robles, & Eastridge, 2000; Piazza, Adelinis, Hanley, Goh, & Delia, 2000; Rapp, 2007; Rozenblat, Brown, Brown, Reeve, & Reeve, 2009). However, current research is limited insofar as few studies have contrasted the relative effectiveness of the two treatments for reducing stereotypy.…”
Section: Introductionmentioning
confidence: 99%
“…That is, clinicians may need to use denser schedules to reduce the behavior in individuals who display very high levels of stereotypy. For example, Rozenblat et al (2009) have shown that the DRO interval may need to be as short as 1 s to reduce vocal stereotypy in children with autism. If dense schedules are required, the clinical utility of DRO and NMS is somewhat compromised because the implementation of treatment may interfere with the occurrence of socially acceptable behaviors (e.g., listening to instructions, completing tasks).…”
Section: Introductionmentioning
confidence: 99%
“…Differential reinforcement of other behavior (DRO) is an intervention used successfully to reduce problem behavior such as self‐injury and motor stereotypy (Beare, Severson, & Brandt, ), stereotypic vocalizations (Rozenblat, Brown, Brown, Reeve, & Reeve, ), and verbal perseverations (Rehfeldt & Chambers, ). Arguably, DRO procedures require the participant to make complex discriminations.…”
mentioning
confidence: 99%